2021
DOI: 10.1371/journal.pcbi.1009126
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing testing for COVID-19 in India

Abstract: COVID-19 testing across India uses a mix of two types of tests. Rapid Antigen Tests (RATs) are relatively inexpensive point-of-care lateral-flow-assay tests, but they are also less sensitive. The reverse-transcriptase polymerase-chain-reaction (RT-PCR) test has close to 100% sensitivity and specificity in a laboratory setting, but delays in returning results, as well as increased costs relative to RATs, may vitiate this advantage. India-wide, about 49% of COVID-19 tests are RATs, but some Indian states, includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Previous studies comparing antigenic and molecular testing regimes to control COVID-19 report that mass antigen testing alone is an acceptable alternative to strategies that include molecular testing 8,9,10 . In agreement, we found that mass antigen testing at a sufficient sensitivity can detect and isolate almost all individuals infected with a concordant variant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies comparing antigenic and molecular testing regimes to control COVID-19 report that mass antigen testing alone is an acceptable alternative to strategies that include molecular testing 8,9,10 . In agreement, we found that mass antigen testing at a sufficient sensitivity can detect and isolate almost all individuals infected with a concordant variant.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this methodology is that it just aims to rank the states and UTs based on their current testing performance and does not take into account the qualitative factors, such as governance, IEC activities, population demographics, and social behavior, which are also important in determining testing outcomes. In future work, the ranking of the states/UTs using this proposed ranking methodology can be used for optimizing the testing performance in poorly performing & low resource regions by integrating a model and channelizing efforts & resources in the right direction (13).…”
Section: Discussionmentioning
confidence: 99%
“… Diagnostic flow chart for COVID-19 disease detection.The probable flow chart used to rule out positive or negative test results forSARS-CoV-2infections in asymptomatic and symptomatic individuals with COVID-19 [ 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ]. …”
Section: Figurementioning
confidence: 99%